Maureen : a Harold Fry novel - Joyce, Rachel (The Dial Press, 2023)
"Maureen Fry has settled into the quiet life she shares with her husband after his iconic walk across England ten years ago. When an unexpected message from the North disturbs her equilibrium again, it is now her turn to make a journey. But Maureen is not like Harold. By turns outspoken, then vulnerable, she struggles to form bonds with the people she meets, and the landscape she crosses has radically changed. And Maureen has no sense of what she will find at the end of the road. All she knows is that she has to get there"--